Description of Physical Activity of Workers in the Hybrid Era - Wafiq Nurul Azizah; Hana Rizmadewi Agustina; Bambang Aditya Nugraha (Jurnal Keperawatan Silampari, 2023)
This study aims to describe the physical activity of workers during the hybrid. The method used is a narrative review with an article search based on the PCC approach on five databases: Garuda, CINAHL, PubMed, Scopus, and ScienceDirect. The studies reviewed were full-text articles published from 2019 - 2022 and published in English or Indonesian. The results showed that six pieces analyzed that WFH can reduce physical activity and hybrid can encourage workers' physical activity by providing flexibility to integrate work, leisure, domestic, and travel activities into daily routines. However, motivational factors, commuting, and changes in work style can also influence workers' physical activity levels during the hybrid. In conclusion, the combination can support workers to do sufficient physical activity with support from the surrounding environment and strong motivation. Keywords: Physical activity, Hybrid, Worker